Older Adults Experiences of Learning to Use Tablet Computers: A Mixed Methods Study - Vaportzis, Eleftheria; Giatsi Clausen, Maria; Gow, Alan J. (Frontiers in Psychology, 2018)
Background: We wanted to understand older adults’ experiences of learning how to use a tablet computer in the context of an intervention trial, including what they found helpful or unhelpful about the tablet training, to guide future intervention studies. Methods: Mixed methods study using questionnaire and focus groups approaches. Forty-three participants aged between 65 and 76 years old from the “Tablet for Healthy Ageing” study (comprising 22 in the intervention group and 21 controls) completed a post-intervention tablet experience questionnaire. Those who completed the tablet training intervention were invited to share their experiences of engaging with new technology in post-intervention focus groups. We conducted three separate focus groups with 14 healthy older adults (10 females). Results: Questionnaire data suggested that the overall experience of the 22 participants who participated in the tablet training intervention was positive. The majority of participants said that it was likely or very likely they would use a tablet in the future. The focus groups’ themes that emerged were related to the perception of tablet training, the experience of using tablets, and suggestions for future studies. Participants mentioned that their confidence was increased, that they enjoyed being part of a social group and downloading applications, but they also felt challenged at times. Advantages of using tablets included the ability to keep in touch with family and friends, a motivation to contribute to community, and the potential for tablets to improve mental abilities and overall health and wellbeing. Participants made suggestions that would enable tablet usage, including improvement of features, and suggestions that would improve future tablet training studies, including smaller classes. Conclusions: Our findings have implications for the development of interventions utilising new technologies that might promote the health and wellbeing of older adults.